Functional evidence for the involvement of GABA(A) receptors in cholecystokinin induced ileal contraction - (:unkn) unknown (NATL RESEARCH COUNCIL CANADA, 1995)
To determine the role of GABAergic neurotransmission in cholecystokinin octapeptide (CCK-8) induced contraction of the guinea pig ileal longitudinal muscle - myenteric plexus preparation, CCKA or CCKB receptors were protected by L 364,718 and L 365,260, respectively. GABA(A) receptors were protected with bicuculline and the remainder of the receptors were inactivated by N-ethylmaleimide. Following the specific treatments isometric contractions in response to CCK-8 (0.1 nM - 1.0 mu M) were obtained. CCKB receptor protection alone abolished responses to CCK-8. Additional GABA(A) receptor protection restored the responses. CCKA receptor protection alone decreased contractile responses to CCK-8, and additional protection of GABA(A) receptors resulted in restoration of the contractile responses at high concentrations of CCK-8. The results suggest that the CCKA and CCKB receptors that mediate the contractile action of CCK differ with regard to GABAergic neurotransmission. CCKB receptors appear to be dependent upon intact GABAergic neurotransmission, whereas CCKA receptors partially utilize this pathway.
Keywords: cholecystokinin receptors; L 364,718; L 365,260; GABA; receptors; PD 135 158; ileum; cholecystokinin antagonists; GUINEA-PIG ILEUM; GAMMA-AMINOBUTYRIC ACID; LONGITUDINAL MUSCLE; MYENTERIC PLEXUS; ANTAGONIST; INTESTINE; RELEASE; GASTRIN; POTENT; NERVES